THE HERITAGE AND NARRATIVE OF CONFUCIAN COURTYARD AND ARCHITECTURE IN SUSTAINABLE DEVELOPMENT IN SHANDONG, CHINA - Rong, Weihan; Bahauddin, Azizi (PLANNING MALAYSIA, 2023)
In recent decades, China has witnessed a miracle of rapid urbanisation, and the development of traditional Chinese architecture has faced challenges as well as opportunities. Improper planning has undermined the well-being of residents, and many historic buildings have been demolished. Under the slogan of “high-quality urban development”, the value of traditional architecture is rarely mentioned. Therefore, research into architectural heritage and urban sustainability is necessary. This study focuses on Shandong Province in China, the birthplace of Confucianism and, to a large extent, the long history of Chinese culture. By studying courtyard architecture under the influence of Confucianism, the aim is to reveal the cultural profile of the new urban era while critiquing the problems in the urban planning process. The study adopts a qualitative method based on the researcher's field investigation and data collection, as well as one-on-one interviews with experts, to collate typical cases for analysis. In addition, this study also intervenes from a narrative perspective to facilitate the exploration of the value of architecture. The findings suggest that courtyard architecture embodies Chinese aesthetic and philosophical thinking, has theoretical and practical implications for living environments, communities, and urban development, and brings new insights that can better achieve sustainable goals while expanding the existing knowledge of architecture and courtyards.